GAMBARAN FUNGSI KELUARGA PADA LANSIA DEPRESI DIDESA TALAPETA KABUPATEN DELI SERDANG - Magda Siringo-ringo; Nasipta Ginting; Febrianis Wau (UNIVERSITAS SARI MUTIARA INDONESIA, 2021)
Introduction:A individual who has reached the age of 60 or above is termed elderly. Depression in the elderly can be caused by a decrease in body physiological functions, a decrease in income, separation, the death of a life partner, and other factors. The attitude, action, and acceptance of the family toward its members is the family's function. The aim:This study was conducted in Talapeta Village, Deli Serdang Regency, to determine the description of family function in elderly depression. The data in this study was collected through a questionnaire, which is a qualitative method. Univariate analysis was used to analyze data. The results stated that the highest proportion of respondents were aged 60-74 years old, with 26 respondents (74.2%); the gender of respondents with the highest proportion of women was 24 respondents (68.6%); the marital status of respondents with the highest proportion of widows was 23 respondents (65.7%); and the education of respondents with the highest proportion not attending school was 18 respondents (51.4% ). In Talapeta hamlet, where there was a high proportion of moderate family function and as many as 16 respondents, family function in elderly depression was studied (45.7 % ). Depression in the elderly might be influenced by demographic variables. Conclusion: In depressed elderly people, family function is moderate. Because the elderly live with their families, this is the case. It is intended that the family would pay attention and play an active role in the care of the elderly.